PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN LIMBAH JAGUNG SEBAGAI BAHAN PUPUK ORGANIK DI DUSUN BONTOREA, DESA TAROWANG, KECAMATAN GALESONG SELATAN, KABUPATEN TAKALAR : PENGABDIAN KEPADA MASYARAKAT - Yunus, Harlina; Herawaty, Herawaty; Rosmiati, Rosmiati; Kurnia , Akhmad (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Abstract Processing corn waste into organic fertilizer can provide multiple benefits, namely reducing agricultural waste dumped into the environment and providing a source of useful organic nutrients for plants. The purpose of the Community Service activities carried out in Bontorea Hamlet, Tarowang Village, South Galesong District, Takalar Regency, South Sulawesi is to increase public knowledge and awareness regarding the processing of corn waste and its benefits as a raw material for organic fertilizer. Through counseling, training, and field demonstrations, it examines methods for processing corn waste into organic fertilizer and analyzes its impacts and benefits in the context of sustainable agriculture. The participatory approach method is used in community service activities to involve farmers and local communities in the entire corn waste processing process. Through training, counseling, and field demonstrations, farmers' knowledge and skills in processing corn waste into organic fertilizer are increased. The results of this service activity show that processing corn waste into organic fertilizer has the potential to reduce environmental pollution, increase agricultural productivity, and increase awareness and community participation of farmer groups in Bontorea Hamlet. Therefore, processing corn waste as raw material for organic fertilizer can be a sustainable and environmentally friendly alternative in managing agricultural waste. Keywords: Waste, corn, Bontorea, Takalar